Stevia, sucralose and sucrose added to a maqui-Citrus beverage and their effects on glycemic response in overweight subjects: A randomized clinical trial - Villaño, Débora; Masoodi, Hedyeh; Marhuenda, Javier; García-Viguera, Cristina; Zafrilla, Pilar (Food science & technology, 2021)
Background: Low-caloric sweeteners represent a good alternative to the extra boost of energy of sugar-sweetened beverages. However, their long-term effects have barely been assessed. In the present study, the influence of low-caloric sweeteners added to a maqui/Citrus beverage on the glycemic profile has been evaluated. Methods: A parallel, randomized and triple blind clinical study was performed in overweight subjects (n = 138), who consumed 330 mL/day of a beverage added with Stevia, Sucralose or Sucrose, for 60 days. Results: BMI did not change significantly with any treatment. Fasting glucose increased after the short-term consumption of Sucrose added beverage (26%), as well as with the addition of the low-caloric sweeteners, but in a lesser extent: 11% for Stevia and 20% for Sucralose. Insulin concentrations did not change significantly with any drink, which resulted in a significant increase in HOMA-IR with Sucralose (p = 0.002) and Sucrose (p = 0.001). Conclusions: The results obtained link the consumption of sucrose sweetened beverages with a disbalance in glycaemic response, and a better response with Stevia addition, although it also produces certain negative effects on glycemic control. The evidence available to date is not conclusive enough to advise the wide use of LCS. ClinicalTrials.gov NCT 04016337. [Display omitted] •Consumption of sucrose-sweetened beverages impairs insulin sensitivity and HOMA-IR.•Consumption of sucrose, sucralose or stevia-sweetened beverages does not alter BMI.•Ghrelin is unaltered after 60-day consumption of any of the sweetened-beverages.